Assessing the knowledge and risk of type 2 diabetes mellitus among university students / Nur Wahida Zulkifli ... [et al.] - Zulkifli, Nur Wahida; Kamaruddin, Nur Ain Nabihah; Wong, Yuet Yen; Idham Abu Hasan, Nurhasniza; Daud @ Ibrahim, Nurulfalahin (Faculty of Pharmacy, 2024)
Type 2 Diabetes mellitus is one of the concerning worldwide non-communicable diseases commonly affecting people ages 40 years old and above. Recent data shows that prevalence of T2DM in adolescent and young adults is increasing. This study aimed to assess the DM-related knowledge among undergraduates, to determine the relationship of sociodemographic factors and DM-related knowledge with DM risk score, and to assess the predictors of DM risk score. A cross-sectional survey was conducted among undergraduates at a public university in Selangor, Malaysia. The questionnaire was divided into two main sections, with section one focusing on demographic data and DM risk assessment using Modified Asian Finnish Diabetes Risk (ModAsian FIDSRISC) Score, and section two focusing on DM-related knowledge. Using convenient sampling method, undergraduates who are ≥ 18 years old and currently pursuing bachelor’s degree of study were included in the study. Undergraduates who were unable to give consent, has been diagnosed with diabetes and pursuing study other than bachelor’s degree were excluded. Pearson-Chi Square test and binary logistic regression analysis were used with significant study of p<0.005. A total of 462 students from various faculties contributed to the study. The mean score of DM-related knowledge obtained from the students was 10.99 ± 4.992 with the majority level of knowledge were found to be moderate (53.2%). Most of students had low risk of DM (61.3%) and only 0.2% had high risk of DM. There were significant relationships between the risk of DM with having relative(s) with DM (p < 0.001, OR = 0.065) and DM-related knowledge (p = 0.029, OR = 1.074). This study showed that students with higher DM risk was associated with good DM-related knowledge, which might contribute to delay prevention and treatment. These results highlight the importance of targeted educational intervention within university curricula to increase the awareness regarding DM among young adults, the future generation of our country.